Student learning about social responsibility in the global textile and apparel industry: the use of video as an instructional tool. Issue 1 (2nd January 2022) - Hwang, Chanmi; Lee, Youngji; Ghalachyan, Armine; Karpova, Elena
ABSTRACT: The purpose of this study was to explore the effectiveness of a documentary video in enhancing student understanding of social responsibility (SR) concept in the context of the textile and apparel industry. A total of 61 college students majoring in apparel design and management participated in the study. The students provided open-ended written responses to a set of questions before, during, and after watching the video. The data were analysed using a content analysis. Word frequency analysis using NVivo software was used to corroborate the findings. The results showed that the video was effective in increasing students' understanding of SR. Further, after watching the video, students demonstrated the willingness to proactively address the SR issues from personal and collective perspectives. The results highlight the effectiveness of video as an instructional tool to help students understand the complex SR concept in the context of the global textile and apparel industry.